Keanekaragaman Jenis Vegetasi Pohon, Estimasi Biomassa dan Serapan Karbon Hutan Lahan Kering di Kampung Selil Distrik Ulilin Kabupaten Merauke Provinsi Papua Selatan - Hutapea, Musa B.; Siallagan, Johnson; Rumahorbo, Basa T.; Manalu, Janviter; A. Asmuruf, Frans (Jurnal Inovasi Global, 2026)
This study aims to analyze the species diversity of tree vegetation and to estimate aboveground tree biomass, calculate carbon stock and carbon sequestration, and assess the contribution of tree diameter classes within a cluster plot in the dryland forest of Selil Village, Ulilin District, Merauke Regency, South Papua Province. This study employed a quantitative-descriptive approach based on a field survey using the National Forest Inventory (Inventarisasi Hutan Nasional/IHN) 2.0 method. Species diversity was analyzed using the Shannon–Wiener index, biomass was estimated using the Chave allometric equation, while carbon stock and carbon sequestration were calculated based on the IPCC conversion factor. The results showed that 64 individual trees representing 7 species were recorded within the cluster plot, namely kelat (Eugenia densiflora), jale (Casuarina papuana), resak (Vatica papuana), kapur (Dryobalanops aromatica), bintangur (Calophyllum papuanum), wild nutmeg (Myristica sp.), and merawan (Hopea papuana). Species diversity was classified as moderate (1 < 1.477 < 3). The most dominant species was kelat (Eugenia densiflora) with an Important Value Index (IVI) of 100.304, followed by resak (Vatica papuana) with 68.522 and jale (Casuarina papuana) with 49.023. The total above ground tree biomass was 141.228 tons/ha, with the largest contribution coming from kelat (Eugenia densiflora), jale (Casuarina papuana), and resak (Vatica papuana). This biomass produced a carbon stock of 66.377 tons C/ha and carbon sequestration of 243.383 tons CO₂/ha. The diameter class of 40 cm up contributed the greatest share to biomass and carbon, accounting for 70.71% of the total biomass. This indicates that large diameter trees play a major role in climate mitigation, are important as natural carbon sinks, and provide baseline data that can be used to support sustainable forest management and climate change mitigation policies in South Papua.